UBC12‐mediated SREBP‐1 neddylation worsens metastatic tumor prognosis. Issue 9 (23rd June 2020) - Heo, Mi Jeong; Kang, Sung Hyun; Kim, Yun Seok; Lee, Jung Min; Yu, Jinha; Kim, Hong‐Rae; Lim, Hyesol; Kim, Kyoung Mee; Jung, Joohee; Jeong, Lak Shin; Moon, Aree; Kim, Sang Geon
Abstract: Activation of sterol regulatory element‐binding protein 1 (SREBP‐1), a master lipogenic transcription factor, is associated with cancer metabolism and metabolic disorders. Neddylation, the process of adding NEDD8 to its substrate, contributes to diverse biological processes. Here, we identified SREBP‐1 as a substrate for neddylation by UBC12 and explored its impact on tumor aggressiveness. In cell‐based assays, SREBP‐1 neddylation prolonged SREBP‐1 stability with a decrease in ubiquitination. Consequently, NEDD8 overexpression facilitated proliferation, migration, and invasion of SK‐Hep1 liver tumor cells. MLN4924 (an inhibitor of the NEDD8‐activating enzyme‐E1) treatment or UBC12 knockdown prevented SREBP‐1 neddylation and tumor cell phenotype change. This effect was corroborated in an in vivo xenograft model. In human specimens, SREBP‐1, UBC12, and NEDD8 were all upregulated in hepatocellular carcinoma (HCC) compared to nontumorous regions. Moreover, SREBP‐1 levels positively correlated with UBC12. In GEO database analyses, SREBP‐1 levels were greater in metastatic HCC samples accompanying UBC12 upregulation. In HCC analysis, tumoral SREBP‐1 and UBC12 levels discriminated overall patient survival rates. Additionally, MLN4924 treatment destabilized SREBP‐1 in MDA‐MB‐231 breast cancer cells and in the tumor cell xenograft. SREBP‐1 and UBC12 were also highly expressed in human breast cancer tissues. Moreover, most breast cancers with lymph node metastasis displayed predominant SREBP‐1 and UBC12 expressions, which compromised overall patient survival rates. In summary, SREBP‐1 is neddylated by UBC12, which may contribute to HCC and breast cancer aggressiveness through SREBP‐1 stabilization, and these events can be intervented by MLN4924 therapy. Our findings may also provide potential reliable prognostic markers for tumor metastasis. Abstract : What's new? The transcription factor sterol regulatory element‐binding protein‐1 (SREBP‐1) serves a key role in lipogenesis and is overexpressed in several cancer types. Its impact on cancer malignancy, however, remains unclear. This study identifies SREBP‐1 as a substrate for neddylation by UBC12, a NEDD8‐conjugating enzyme. Neddylation stabilized SREBP‐1, which was accompanied by decreased ubiquitination. Moreover, levels of SREBP‐1 and UBC12 were significantly elevated in metastatic human hepatocellular carcinoma (HCC) and breast cancer specimens and were further associated with patient survival. The findings suggest that increases of SREBP‐1 and UBC12 contribute to aggressive characteristics and overall progression of HCC and breast cancer.